The Efficacy and Safety of Azithromycin for Patients with Cystic Fibrosis: A Systematic Review - Luh Adi Kusuma Suardiani; Fauna Herawati; Ni Made Suastini Suastini (Jurnal Ilmiah Kesehatan, 2022)
Chronic inflammation of the lungs is a major cause of morbidity and mortality in patients with cystic fibrosis. One of the macrolides, azithromycin has antimicrobial, immunomodulatory, and anti-inflammatory effects that are useful in diseases with chronic inflammatory processes such as cystic fibrosis. This systematic review aimed to determine the efficacy and safety of azithromycin administration for cystic fibrosis patients in improving lung function. Pulmonary function was assessed by measuring the value of forced expiratory volume in one second (FEV1) in patients after intervention. The process of searching literature through PUBMED and Cochrane Library uses the keywords "Cystic Fibrosis" and "Azithromycin" with the Boolean operator "AND". There were seven studies selected, with criteria RCT studies, patients of all ages, patients with cystic fibrosis, and compared azithromycin with placebo. After reviewing seven studies, 71.4% of the studies stated that there was a significant increase of mean FEV1 value after being given azithromycin therapy. Other outcomes assessed were FVC values, pro-inflammatory indicators, exacerbations, changes in body weight, and quality of life. Azithromycin administration is considered relatively safe and well-tolerated by patients.